Peran Keluarga Dalam Membangun Karakter Anak Usia Dini - Eri Subaeri Ahmad (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2020)
This research aims to explore the role of the family in shaping the character of early childhood. The method used is qualitative analysis with a literature study approach. The results are as follows: character education is a way to make Indonesian children and their people have commendable and civilized moral behavior. In reality, there are still school children who do not have noble character. One of the contributing factors is the lack of a moral basis that parents instill in the child's self and soul. Building character in early childhood is not as easy as turning the palm of the hand. It needs a very careful approach. The role of parents is very necessary because they are the first to interact with children. The things that parents teach at an early age will form the basis of the child's character and will continue to carry over until he grows up. Parents need to introduce good things to children as the basis for forming their character and morality.